MANAJEMEN UPAYA MENINGKATKAN MINAT BELAJAR DAN KREATIVITAS ANAK DI MASA PANDEMI COVID-19 PADA YAYASAN ISLAM AL AKHYAR - Fahmi Susanti; Amelia Oktaviani; Dewi Kurnia; Hendra Kautsar R; Ika Safitri (Jurnal Lokabmas Kreatif : Loyalitas Kreatifitas Abdi Masyarakat Kreatif, 2021)
This service is in collaboration with the Al-Akhyar . Islamic Foundation This study aims to determine the level of interest in learning and creativity of children during the COVID-19 pandemic with online or online learning models. The results of the study can be concluded, that learning in the era of the covid-19 pandemic, the level of interest in learning and creativity in the children of the Al-Akhyar Islamic Foundation has decreased. With online or online learning, it is not entirely possible for children to learn to understand from this learning. But at least learning through online or online learning can increase interest in learning and creativity in these children.